PENGARUH WAKTU PENGADUKAN TERHADAP WAKTU GELASI BAHAN CETAK ALGINAT - Audia Tria Putri; Rizanda Machmud; Murniwati Murniwati (Faculty of Dentistry Universitas Andalas, 2016)
Alginate is one of many dental materials that used for the impressing materials. Mixing time is one of factorsthat affected the setting time. The aim of this study was to determine the effect of mixing time at 30 seconds, 35seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds and 60 seconds on setting time of alginate. This studyused experimental method. The samples that used were 42 samples and divided into 7 groups of mixing time,that were 30 seconds (control), 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, and 60 seconds.Setting time was tested with acrylic test rod based on ADA specification no.18. The alginate powder was mixedwith water (10 gr : 23 ml ratio), then put in the mould. Acrylic test rod was placed in contact with the surface ofalginate dough. The setting time was measured from the starting of the mix to the time when alginate does notadhere to the end of the rod. Result of this study showed that the average of setting time of alginate which mixedfor 30 seconds (control), 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, and 60 seconds was120.17 ± 3.312 seconds, 119.00 ± 1.265 seconds, 118.17 ± 1.472 seconds, 114.83 ± 3.896 seconds, 112.00 ±1.673 seconds, 109.17 ± 0.983 seconds, and 105.33 ± 4.082 seconds respectively. One Way Anova test shows significant difference among all experimental group with p=0.000. The change of setting time alginate show significant difference with control group when it mixed for 45 seconds, 50 seconds, 55seconds, and 60 seconds.Keywords: alginate, mixing time, setting time